2015
DOI: 10.1155/2015/829195
|View full text |Cite
|
Sign up to set email alerts
|

Induced Hypothermia Does Not Harm Hemodynamics after Polytrauma: A Porcine Model

Abstract: Background. The deterioration of hemodynamics instantly endangers the patients' life after polytrauma. As accidental hypothermia frequently occurs in polytrauma, therapeutic hypothermia still displays an ambivalent role as the impact on the cardiopulmonary function is not yet fully understood. Methods. We have previously established a porcine polytrauma model including blunt chest trauma, penetrating abdominal trauma, and hemorrhagic shock. Therapeutic hypothermia (34°C) was induced for 3 hours. We documented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Combined trauma resulted in severe shock associated with a fourfold increase of lactate levels in both trauma groups (74.6 mg/dl vs. 18.6 mg/dl in the sham groups; p<0.001) (Figure 2 Another approach of this study concerning a detailed analysis of how induced hypothermia influences haemodynamics has been previously published (24). In brief, that work showed that MAP dropped significantly after trauma induction and normalized temporarily after volume resuscitation.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…Combined trauma resulted in severe shock associated with a fourfold increase of lactate levels in both trauma groups (74.6 mg/dl vs. 18.6 mg/dl in the sham groups; p<0.001) (Figure 2 Another approach of this study concerning a detailed analysis of how induced hypothermia influences haemodynamics has been previously published (24). In brief, that work showed that MAP dropped significantly after trauma induction and normalized temporarily after volume resuscitation.…”
Section: Resultsmentioning
confidence: 70%
“…In brief, that work showed that MAP dropped significantly after trauma induction and normalized temporarily after volume resuscitation. Hypothermia neither influenced the MAP nor necessitated catecholamines (24). The induction of trauma and volume resuscitation led to haemodilution.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…This large animal model is reproducible and clinically relevant traumatic insult with controlled hemorrhage. Using this model, the role of induced hypothermia (34°C) for 3 h has been studied and revealed no relevant effects of therapeutic hypothermia on hemodynamics and coagulation system . However, hypothermic animals showed reduced hepatic inflammatory response .…”
Section: Comorbidities Influencing Fracture Healingmentioning
confidence: 99%